Peningkatan Hasil Belajar Akidah Akhlak Menggunakan Model Kooperatif Tipe STAD pada Siswa Madrasah Tsanawiyah - Siti Patimah; Khermarinah Khermarinah (Jurnal Indonesia Kajian Pendidikan Islam, 2025)
Background: This study was motivated by the low learning outcomes of grade X IPS-2 students in the Akidah Akhlak at MAS Mansyaul Ulum, even though this subject is important for students' character and moral development. Objective: This study aims to improve the learning outcomes of grade X IPS-2 students in the Akidah Akhlak subject at MAS Mansyaul Ulum through the Student Team Achievement Division (STAD) cooperative learning model. Method: The research design used Classroom Action Research (CAR) conducted in three cycles, each consisting of planning, implementation, and reflection, with 21 students as subjects. Data were collected through observation and learning achievement tests and analyzed quantitatively based on the Minimum Competency Criteria (KKM) of 75%. Results: There was a significant increase in student activity and learning outcomes: in the first cycle, student activity was 54.2% with learning outcomes of 28.57%; in the second cycle, activity increased to 71.42% with learning outcomes of 66.67%, and in the third cycle, activity reached 95.23%, with 100% of students achieving the MCC and an average class score of 91.42. Conclusion: The STAD model effectively improves student activity and learning outcomes in Akidah Akhlak. Contribution: This study contributes as a cooperative model that can enhance student engagement in learning based on moral and religious values.